A Game-based Assessment as A Formative Test in Academic Performance: Teachers’ Perspectives on Kahoot! - Muna, Hayatul; Setiyana, Rusma; Ismail, Fitriah (Universitas Teuku Umar, 2023)
This study explored the utilization of a game-based assessment tool, Kahoot, as a formative test in the academic context focusing on the perspectives of teachers. With the increasing integration of technology into education, Kahoot has gained popularity as an interactive and engaging platform for assessing student learning. The research investigated how teachers perceive Kahoot as a formative assessment tool and its impact on their teaching practices. The qualitative approach was used in this study. Moreover, purposive sampling was administered to determine the subjects. The data in this study was collected through surveys and interviews with five lecturers of the Faculty of Education and Teacher Training of IAIN Lhokseumawe form different departments, namely; English Department, Arabic Department, and Indonesian Department to gain insights into their experiences and perspectives. The findings showed that teachers have a positive perspective on the utilization of kahoot as a formative test in academic performance. The results also revealed the advantages and challenges associated with using Kahoot as a formative test and shed light on its effectiveness in promoting active learning and student engagement. A gamed-based assessment called kahoot, facilitates teachers to save their time in assessing students’ comprehension through immediate feedback. Its accessibility simplifies teachers and students to do a test at every turn. Therefore, this research provides valuable insights into the practical use of game-based assessments in the academic setting and the implications for pedagogical approaches.